A novel box for aerosol and droplet guarding and evacuation in respiratory infection (BADGER) for COVID-19 and future outbreaks - Hau D. Le (Nature Portfolio, 2021)
Abstract The coronavirus disease 2019 (COVID-19) pandemic caused by the severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) has infected millions and killed more than 1.7 million people worldwide as of December 2020. Healthcare providers are at increased risk of infection when caring for patients with COVID-19. The mechanism of transmission of SARS-CoV-2 is beginning to emerge as airborne spread in addition to direct droplet and indirect contact as main routes of transmission. Here, we report on the design, construction, and testing of the BADGER (Box for Aerosol and Droplet Guarding and Evacuation in Respiratory Infection), an affordable, scalable device that contains droplets and aerosol particles, thus minimizing the risk of infection to healthcare providers. A semi-sealed environment is created inside the BADGER, which is placed over the head of the patient and maintains at least 12-air changes per hour using in-wall vacuum suction. Multiple hand-ports enable healthcare providers to perform essential tasks on a patient’s airway and head. Overall, the BADGER has the potential to contain large droplets and small airborne particles as demonstrated by simulated qualitative and quantitative assessments to provide an additional layer of protection for healthcare providers treating COVID-19 and future respiratory contagions.